School and community. The Colombian experience with Student Social Service Projects. - Ortega Torres, W. Eduardo; Vahos Anaya, M. Alejandra; Sánchez Medina, José Antonio (IJERI: International Journal of Educational Research and Innovation, 2020)
One of the most difficult problems that the school is currently facing is that it generates encapsulated knowledge and learning processes that are disarticulated from the characteristics of the context which defines students. Against this background, it is proposed that learning- service can become an alternative that manages to articulate the knowledge of the school with the community in order to generate authentic learning processes. Based on these premises, this article presents a practical study on Student Social Service Projects (SSSP), as an alternative to overcome the dualistic school-community vision. The SSSP is a state requirement that every student from public or private education in Colombia must meet in the upper grades and which, from the theory, is recognized as a scenario of articulation between the school, the community, and the individual. However, the findings show a series of difficulties that have limited its educational scope and reveal a historically fragmented and lacking national educational system, from which the school needs to be rethought and re-signified to strengthen the learning and training processes of students.